The Influence of Democratic Leadership Style, Work Engagement, and Work Environment on Employee Performance at the Bangkalan Pratama KPP - Yolanda Dewita Sari; Kuswandi; Sri Rahayu; Rifda Fitrianty (International Publisher, 2025)
This study examines the influence between democratic leadership style, work engagement, and work environment on employee performance at KPP Pratama Bangkalan. The sample in this study involved the entire existing population, namely 77 employees at the Bangkalan Primary Tax Service Office. The data collection technique used in this study was a Likert scale questionnaire. This study uses SPSS analysis tools as a data processing method. This research data analysis uses multiple linear regression. The results showed that partially the variables of democratic leadership style, work engagement, and work environment had a significant effect on employee performance at KPP Pratama Bangkalan. Then simultaneous testing shows that the variables of work engagement, performance allowances, and job training affect employee performance at KPP Pratama Bangkalan.